(untitled) (Research, Society and Development, 2020)
The aim of this paper was to describe the epidemiological profile of violence against children and adolescents in the state of Paraiba. It was a descriptive, retrospective, quantitative and documentar study. The data used was collected from the Notifiable Diseases Information System (SINAN), registered in the state of Paraiba, between the years 2009 and 2017, involving the age group from 0 to 19 years and available in TabNet – Domestic, Sexual and/or Others Violence. The variables used were: year of registration, age and sex of the victim, type of violence perpetrated, place of occurrence of the fact and type of bond with the aggressor. It was found that the victim’s sex and age group were associated (p <0.001) with the characteristics of violence. Female children and adolescents were more susceptible to sexual violence (20.1%), when compared to male ones (2%), being the main aggressor the (ex)partner (21,6%). In terms of age, until 10 years old, negligence (75%) was the most frequent type of violence, commited by father and/or mother (28.4%) in their own residence (77.6%). In the 10 to 19 age group, the most common violence was physical (63.6%), on streets (42.5%), and committed by friends (21.9%) or strangers (37.4%). It was concluded that the notifications were associated with the male gender (54.6%), in the age groups of 15 to 19 (38.3%) and 1 to 4 years old (24.2%), with a predominance of physical violence ( 42.6%), committed by a stranger (32.1%), at the victim’s residence (51%).